Field‐scale observations of a transient geobattery resulting from natural attenuation of a crude oil spill. Issue 4 (24th April 2017) - Heenan, J. W.; Ntarlagiannis, D.; Slater, L. D.; Beaver, C. L.; Rossbach, S.; Revil, A.; Atekwana, E. A.; Bekins, B.
Abstract: We present evidence of a geobattery associated with microbial degradation of a mature crude oil spill. Self‐potential measurements were collected using a vertical array of nonpolarizing electrodes, starting at the land surface and passing through the smear zone where seasonal water table fluctuations have resulted in the coating of hydrocarbons on the aquifer solids. These passive electrical potential measurements exhibit a dipolar pattern associated with a current source. The anodic and cathodic reactions of this natural battery occur below and above the smear zone, respectively. The smear zone is characterized by high magnetic susceptibility values associated with the precipitation of semiconductive magnetic iron phase minerals as a by‐product of biodegradation, facilitating electron transfer between the anode and the cathode. This geobattery response appears to have a transient nature, changing on a monthly scale, probably resulting from chemical and physical changes in subsurface conditions such as water table fluctuations. Key Points: This study shows evidence of a biogeobattery observed in the field